Regional classifications of the agricultural sector: the case of Southern - Central Russia - Dimitrios G.; Belokrilova O.S.; Shevchenko I.V.; Iakovlev A.; Chepurko Y. (Selected readings on economies in transition, 2000)
Indices of the external environment get special attention because of their all-inclusive nature which focuses on location specific characteristics. An analysis of producers decision making indicates that the weights used for the regional characteristics considered and included in the index should not vary across regions. Given this, a quality of the external business environment index for the agricultural sector is computed for the Southern - Central part of Russia. All regional characteristics considered are scaled from 0 - 100, so that the index is independent of units of measurement; the regional characteristics incorporated in the index are variables of the external business environment of each country that may affect production costs and the possibilities for a development of the agricultural sector. According to the adopted index/criterion, Krasnodar Krai is on the top of the ranking followed by Kursk Oblast, Samara Oblast, Astrakhan Oblast, Saratov Oblast, Voronezh Oblast, Rostov Oblast, Stavropol Krai, Volgograd Oblast, Belgorod Oblast, Ulyanovsk Oblast, Lipetsk Oblast, Tambov Oblast, and Penza Oblast.